Ocurrence of Campylobacter spp. in chilled chicken carcasses slaughtered in the west region of Santa Catarina, Brazil - Bortoli, William; Bortoli, Elaine da Silva; Dalmina, Karine Andrezza; Melo, Fernanda Danielle; Costa, Ubirajara Maciel da; Ferraz, Sandra Maria (Acta Scientiae Veterinariae, 2017)
Background: The thermophilic bacteria of the genus Campylobacter are important agents of alimentary gastroenteritis, called campylobacteriosis. These microorganisms multiply in temperatures ranging from 25ºC to 46ºC, however, low temperatures are incompatible with their multiplication. For this reason, the seasons of the year may interfere with the level of contamination by Campylobacter sp. The main sources of transmission are contaminated meat and giblets from poultry during poorly conducted slaughter operations. The disease may present itself with a different range of forms of disease: from mild signs of gastrointestinal infection to more severe cases, such as the Guillain-Barré syndrome. Material, Methods & Results: Due to the great importance of western Santa Catarina to the poultry industry, it was necessary to verify the occurrence of the pathogen in cold carcasses of broilers slaughtered in this region, and its variation through the seasons of the year. From January 2013 to February 2015 broiler carcasses were collected weekly, after the water cooling process, in slaughterhouses under Federal Inspection of the three largest microregions of western Santa Catarina in terms of number of broilers slaughtered, totaling 808 samples. The assessment of thermophilic Campylobacter was performed according to the methodology recommended by ISO 10272-1: 2006. Of the 808 samples analyzed, the frequency of isolation of thermophilic Campylobacter was 1.82% (8/440) in microregion 1, 4.95% (10/202) in microregion 2 and 13.86% (23/166) in the microregion 3, totaling 5.07% of positive samples (41/808). Comparing the microregions, it was verified that there was no significant difference (P > 0.05) between the isolation frequencies of microregions 1 and 2. However, there was a significant difference (P < 0.05) between the isolation rates of Microregion 3 in relation to microregions 1 and 2. Microregion 1 presented the lowest percentage of Campylobacter thermophilic isolates. Discussion: Although the rates found are lower than expected when compared to those already published, consumption of these products may provide risks to consumers, mainly through cross-contamination of foods that will be consumed raw, requiring greater controls in the entire poultry industry in order to ensure a safe product for the consumer. Analyzing each season of the year individually (winter and summer), 5.88% (14/238) of the samples processed during summer (October to March) were positive for the assessed microorganism and in 4,74% (27/570) of the samples analyzed in the winter (April to September), the presence of thermophilic Campylobacter was detected. Nevertheless, there was no significant difference (P > 0.05) between the seasons. However, it is evident the need for a longer study to evaluate the actual influence of the seasons (winter and summer) on the isolation rate of thermophilic Campylobacter in broiler carcasses shortly after the cooling process. Even though the study demonstrated low levels of thermophilic Campylobacter isolation rates in the evaluated regions, just the fact of isolating the agent already shows that there is an imminent risk to consumers, mainly due to cross-contamination of foods that will be consumed raw; therefore, higher standards of microbiological controls should be practiced in the production chain and slaughter of poultry, respecting good manufacturing practices, hygiene and handling practices within the industry.